Not your average zombie : rehumanizing the undead from voodoo to zombie walks - Kee, Chera (University of Texas Press, 2017)
The zombie apocalypse hasn?t happened?yet?but zombies are all over popular culture. From movies and TV shows to video games and zombie walks, the undead stalk through our collective fantasies. What is it about zombies that exerts such a powerful fascination? In Not Your Average Zombie, Chera Kee offers an innovative answer by looking at zombies that don?t conform to the stereotypes of mindless slaves or flesh-eating cannibals. Zombies who think, who speak, and who feel love can be sympathetic and even politically powerful, she asserts. Kee analyzes zombies in popular culture from 1930s depictions of zombies in voodoo rituals to contemporary film and television, comic books, video games, and fan practices such as zombie walks. She discusses how the zombie has embodied our fears of losing the self through slavery and cannibalism and shows how "extra-ordinary" zombies defy that loss of free will by refusing to be dehumanized. By challenging their masters, falling in love, and leading rebellions, "extra-ordinary" zombies become figures of liberation and resistance. Kee also thoroughly investigates how representations of racial and gendered identities in zombie texts offer opportunities for living people to gain agency over their lives. Not Your Average Zombie thus deepens and broadens our understanding of how media producers and consumers take up and use these undead figures to make political interventions in the world of the living.